THE NEW ORGANIC-MINERAL FERTILIZER FOR GRAIN CROPS - A. I. Ivanov; Zh. A. Ivanova; I. V. Sokolov; I. A. Freydkin (Зерновое хозяйство России, 2019)
The problem to provide the livestock industry of the North-West of Russia with forage grain has sharply escalated since 2010. Its successful solution is connected with the level and validity of the use of mineral and organic fertilizers. The purpose of the study, started by the Menkovsky Branch of the AFI in 2012, was to find effective options for the use of new organic-mineral fertilizer (OMF) which provides maximum agronomic effect and can produce grain of high quality. The methodological basis was the micro trials in polyethylene vessels without bottoms of 1 × 1 × 0.4 m in size with an artificially formed upper part of the profile of degraded sandy sod-podzolic soil. The soil was of 4.75 рНKCl, 3.46 mmol (eq) of Ng per100g, 3.20 mmol (eq) of Sch per100g, 1.83% of humus, 217 mg / kg of mobile compounds of phosphorus and 92 mg / kg of potassium. In the course of research, there was high agronomic efficiency of its use for winter wheat and satisfactory agronomic efficiency of its use for barley. When the winter wheat variety ‘Moskovskaya 56’ was fertilized with 5 t/ha of organic-mineral fertilizer containing 2.46% of Ng, 4.51% of P₂O₅ and 3.36% of K₂O, grain yield increased in 2.6 times. Fertilized with N75P50K50 the productivity improved in 3.8 times with a payback of 1 kg of NPK 7.4 and 5.6 grain units, respectively. It has been established that the combination of OMF with mineral fertilizers is accompanied by a significant yield increase with a decrease in its relative contribution from 153% to 59% and from 143% to 105% and a payback of 1 kg of NPK from 3.8 to 2.6 and from 6.9 to 4.7 of barley grain units and winter wheat grain units, respectively. The best indicators of the agronomic efficiency of OMF, both when applied in pure form and when fertilized with N75P50K50, corresponded to a dose of 4 t / ha. It has been found that the addition of 10 kg of potassium (К₂О) per 1 ton to OMF provided yield increase on 15% and the payback period of 1 kg NPK increased from 6.4 to 8.4 grain units. Qualitative indicators of wheat and barley grain fertilized with OMF improved due to the rise of raw protein percentage on 8–27% and a number of ash elements, such as CaO (from 0.07 to 0.11 mg/kg), MgO (from 0.16 to 0.21 mg/kg), Zn (from 21.5 to 23.6 mg/kg).